2013
DOI: 10.3109/13880209.2013.802352
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of ginseng total saponins against hepatic ischemia/reperfusion injury in experimental obstructive jaundice rats

Abstract: Context: Ginseng, the root of Panax ginseng C.A. Meyer (Araliaceae), is one of the most extensively used herbs for stroke and chronic debilitating conditions in East Asian countries. Ginsenosides (GS) are the main bioactive compounds for ginseng's efficacy, but the mechanisms have not been fully clarified. Objective: To investigate hepatoprotective effects of GS against ischemia/reperfusion (IR) injury in the experimental obstructive jaundice rats. Materials and methods: GS was fed to cholestatic rats with IR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Numerous studies have shown that ginseng contributes to EGFR and BCL2 signaling [ 31 , 32 , 33 , 34 ]. Sathishkumar et al [ 32 ] used P. ginseng to develop inhibitors for the EGFR tyrosine kinase domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that ginseng contributes to EGFR and BCL2 signaling [ 31 , 32 , 33 , 34 ]. Sathishkumar et al [ 32 ] used P. ginseng to develop inhibitors for the EGFR tyrosine kinase domain.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that P. ginseng can be used to design new EGFR tyrosine kinase inhibitors. Fu et al [ 34 ] showed that the total saponins in ginseng can protect against hepatic ischemia/reperfusion injury in experimental obstructive jaundice rats.…”
Section: Discussionmentioning
confidence: 99%
“…Measures to overcome ischemia/reperfusion-induced hepatic injury are needed for successful liver transplant. The PG saponin fraction attenuates ischemic reperfusion injury in experimental obstructive jaundice rats; it was found to reduce ALT, AST, and MDA levels [79]. PN saponin preconditioning protects liver grafts in rats from ischemia-reperfusion injury through the ananti-apoptotic pathway [80].…”
Section: Multiple Efficacies For Hepatic Injuriesmentioning
confidence: 99%
“…Ginseng has been used in traditional medicine for many years, especially in East Asian countries. 1 So far, more than 30 ginsenosides have been defined. 2 , 3 Ginsenoid-Rd [dammar-24(25)-ene-3β, 12β, 20(S)-triol-(20-O-β-D-glucopyranosyl)-3-O-β-D-glucopyranosyl-(1→2)-β-D-glucopyranoside] is one of the basic active substances of ginsenoids.…”
Section: Objectivementioning
confidence: 99%
“…In modern medicine, ginsenoids obtained from ginseng plants are decomposed in such a manner that they can be used either in vitamin extracts or in hard gelatin capsules that contain a specified dose. 1 - 3…”
Section: Objectivementioning
confidence: 99%